A street cart called Hope - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Often a thorn in the flesh and the oh-so-tidy minds of city traffic and hygiene departments, food vendors serve a burdgeoning market and not just the poor amid annual city growth rates of 10%. The sector, about as informal as can be, provides...